The elimination of local public animal protection bodies: the case of the Special Secretary of Animal Rights (SEDA) of the Municipality of Porto Alegre, Brasil - Luciano Rocha Santana (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
This essay deals with the elimination of the Special Secretary for Animal Rights (SEDA) of Porto Alegre, which occurred in January 2017 through the Administrative Reform Law of this municipality. The Law in question merged the Municipal Secretary of Urbanism (SMUrb), the Municipal Secretary of Environment (SMAM) and the Special Secretary of Animal Rights (SEDA) in a single agency: Municipal Secretary of Environment and Sustainability (Smams).